Effect of TTC-MMP12184-225 vaccine against lung cancer and associated mechanisms - HUANG Huan, LIU Fengjun, WANG Shan, LI Xu, WANG Bin (精准医学杂志)
Objective To investigate the effect of the TTC-MMP12184-225 vaccine, which is derived from matrix metalloproteinase 12 (MMP12) and tetanus toxin C-fragment (TTC), for the treatment of lung cancer and the underlying mechanisms. Methods The Tumor Immune Estimation Resource (TIMER) database was used to analyze the relative mRNA expression of MMP12 in the tumor tissues and adjacent normal tissues of patients with lung cancer. A subcutaneous tumor model of lung cancer was established by subcutaneously inoculating Lewis lung carcinoma (LLC) cells at 2-3 cm below the right axilla of 6-8 week-old C57BL/6J female mice. When the tumor volume reached approximately 100 mm3, the lungs and tumors were isolated to determine the mRNA expression of MMP12 by RT-qPCR. The CD8+T cell epitopes, CD4+T cell epitopes, and B cell epitopes of MMP12 were predicted on the NetCTL-1.2, SYFPEITHI, and SVMTrip websites, respectively. The immunogenicity of the dominant epitopes was analyzed using the VaxiJen-2.0 server. The secondary structure and hydrophilicity of MMP12 were analyzed by using DNAstar software. TTC-MMP12184-225 protein was synthesized through the Escherichia coli prokaryotic expression system, and the product was identified with Coomassie blue staining. Subcutaneously inoculated with LLC cells at 2-3 cm below the right axilla, a group of 6-8 week-old C57BL/6J female mice were randomized to receive intramuscular injection of 100 μL PBS containing either 20 μg TTC (control group) or 20 μg TTC-MMP12184-225 (experimental group), once every 7 d for a total of 3 times. On the third day after the last injection, the tumors were isolated for volume measurement; the proportions of CD4+T cells and CD8+T cells in tumors were determined by flow cytometry; and the relative mRNA expression levels of C-C motif chemokine ligand 5 (CCL5), C-X-C motif chemokine ligand 9 (CXCL9), interleukin-2 (IL-2), interferon gamma (IFN-γ), granzyme B (GRZB), and perforin (PFP) in tumors were measured by RT-qPCR. Results The TIMER and RT-qPCR results showed that the expression of MMP12 was significantly increased in both patients with lung cancer and the mouse model of lung cancer compared with adjacent normal tissues and lung tissues (P<0.001、0.05). The epitope prediction results showed that MMP12184-225 contained 12 CD8+T cell epitopes, 9 CD4+T cell epitopes, and 3 B cell epitopes. The VaxiJen-2.0 analysis results showed that the immunogenicity score of MMP12184-225 was 0.61. The DNAstar analysis showed that MMP12184-225 was composed of hydrophilic peptides mainly consisting of β-turns. The Coomassie blue staining results showed that TTC-MMP12184-225 protein exhibited a clear band below the relative molecular mass of 60 000. Compared with those in the control group, the mice in the experimental group showed a significantly reduced tumor volume, significantly increased proportions of CD4+T cells and CD8+T cells in tumors, and significantly increased relative expression levels of CCL5, CXCL9, IL-2, IFN-γ, GRZB, and PFP mRNA in tumors (t=2.57-4.60,P<0.05). Conclusion The TTC-MMP12184-225 vaccine exerts an anti-lung cancer effect by promoting the recruitment of CD4+T cells and CD8+T cells and increasing the expression of antitumor-related cytokines in tumor tissues.